2019
DOI: 10.1097/dbp.0000000000000630
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Media Device Use is Associated with Expressive Language Delay in 18-Month-Old Children

Abstract: : Objective: The objective was to examine the association between mobile media device use and communication delays in 18-month-old children. Methods: A cross-sectional study was conducted from September 2011 and December 2015 within the TARGet Kids! primary care research network. Children were included if parents reported their child's mobile media device use and completed a validated questionnaire for communication delay at the 18-month well child visit. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 29 publications
3
50
3
3
Order By: Relevance
“…In this age group, screen time is not recommended at all [1,4]. However, previous studies across different settings have shown that screen time is high in this age group, and detrimentally associated with adiposity, motor development, and language development [11,12,23]. A few mothers thought that screen time was beneficial for infants, providing opportunities for learningparticularly language.…”
Section: Discussionmentioning
confidence: 99%
“…In this age group, screen time is not recommended at all [1,4]. However, previous studies across different settings have shown that screen time is high in this age group, and detrimentally associated with adiposity, motor development, and language development [11,12,23]. A few mothers thought that screen time was beneficial for infants, providing opportunities for learningparticularly language.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies and a very recent meta-analysis showed associations between excessive TV viewing in early childhood and language, cognitive and socio-emotional delay; possible mechanisms responsible for this association would be inappropriate content, decrease in parent-child interaction and poor family functioning. Furthermore, earlier age of media use onset, cumulative hours of media use and contents were independent predictors of poor cognitive and linguistic skills [31,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review examining the relationship between sedentary behaviour and cognitive development (n=96 studies) found unfavourable or no association between screen time and cognitive development, and favourable or no association between reading/storytelling and cognitive development, but due to heterogeneity, meta-analyses were not possible 49. A recent cross-sectional study from our group showed mobile screen use was associated with increased risk of communication delays in infants aged 18 months 50. Furthermore, according to a systematic review (n=26 studies), poor sleep quality and inadequate quantity (ie, chronic sleep deprivation) among children aged 1–17 years were related to worse behavioural and/or cognitive outcomes, but the strength of the association was low and there was a high degree of heterogeneity 51.…”
Section: Introductionmentioning
confidence: 91%